Understanding Ghana's growth success story and job creation challenges - Ernest Aryeetey; William Baah-Boateng (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Ghana's status as one of the African Lions is linked to the country's remarkable growth performance, which culminated in the attainment of lower middle-income status. However, employment response to growth has been weak. Additionally, growth has been accompanied by substantial reduction in poverty, albeit increasing inequality. This development is explained by a slower growth in high labour absorption sectors of agriculture and manufacturing as against high growth in low employment generating sectors of mining and oil extraction. Fixing the problem of the missing middle of dwindling manufacturing and raising productivity in agriculture are recommended for the promotion of growth inclusiveness.
Keywords: J09; J11; J21; O40; O55; 330; elasticity; employment; Ghana; growth; inequality; labour productivity